2022
DOI: 10.3389/fmed.2022.810189
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune effects of anesthetics and their intracellular targets in tumors

Abstract: According to the result released by the World Health Organization (WHO), non-communicable diseases have occupied four of the top 10 current causes for death in the world. Cancer is one of the significant factors that trigger complications and deaths; more than 80% cancer patients require surgical or palliative treatment. In this case, anesthetic treatment is indispensable. Since cancer is a heterogeneous disease, various types of interventions can activate oncogenes or mutate tumor suppressor genes. More and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 115 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…The surgery is accompanied by total anesthesia, which negatively affects the host's immune system. It has been shown that total anesthesia can cause immunosuppression, which in turn could affect the viral activity and could aid the prolongation of HPV persistence [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surgery is accompanied by total anesthesia, which negatively affects the host's immune system. It has been shown that total anesthesia can cause immunosuppression, which in turn could affect the viral activity and could aid the prolongation of HPV persistence [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this field, 292 institutions published papers and 410 inter-agency collaborations were established. The top five universities, based on the number of papers issued, were Harvard University (12), Boston Children's Hospital (10), Harvard Medical School (9), National Institute of Health and Medicine (Inserm) (7), and Fudan University (6). The National Institute of Health and Medical Research (Inserm) and Florida State University System Center were ranked first with a centrality score of 0.01 (Figure 4B), (Table S1).…”
Section: Analysis Of Publication Trendmentioning
confidence: 99%
“…Presently, numerous research groups are directing their attention towards the impact of anesthetic drugs on immune function, postoperative mortality, and recurrence rate of cancer surgery patients. [8][9][10][11][12] A comprehensive investigation of the effect of anesthetic drugs on immune function holds significant implications for perioperative medication in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, procaine inhibited the growth of liver cancer cells. It efficiently regulated DNA methylation in stomach cancer, suggesting it could be a candidate drug for cancers [8]. The non-nucleoside compounds present in local anesthetics function as inhibitors of DNA methyltransferase (DNMT) activity, thereby influencing the expression of micro-RNAs and suppressing histone acetylation.…”
Section: Local Anestheticsmentioning
confidence: 99%
“…Furthermore, the vitro experiments showed that inhalation anesthetics could control immune cells' ability to identify antigens, recruit inflammatory cells, and influence immunological responses carried out by cells. However, due to the dose-dependent effect, sevoflurane and desflurane caused suicide of adaptive immune cells, causing immune suppression [8].…”
Section: Anesthesia and The Immune System's Impact On Cancermentioning
confidence: 99%